THE APPLICATION OF THE PRINCIPLE OF KHIYAR IN ONLINE SALES TRANSACTIONS: A COMPARATIVE STUDY OF ISLAMIC ECONOMIC LAW AND LAW NO. 8 OF 1999 ON CONSUMER PROTECTION - Yuniartik (ADISAM Publisher, 2026)
The transformation of the global economic landscape through the e-commerce ecosystem has triggered a shift in consumer behavior from physical (brick-and-mortar) markets to the digital space. However, the remote and intangible nature of digital transactions presents legal challenges in the form of information asymmetry, which places consumers in a position of unequal bargaining power, particularly regarding the risks of hidden defects and discrepancies in product descriptions. This study aims to examine and compare consumer protection in e-commerce between national positive law and Sharia Economic Law. The research method used is a normative legal (literature review) approach, employing both a comparative approach and a conceptual approach. The results of the study indicate that both legal systems share a philosophical common ground in upholding transactional justice and reducing information asymmetry. Substantively, the regulations on the right to information and compensation in Articles 4 and 7 of Law No. 8 of 1999 on Consumer Protection (UUPK) as well as the PMSE Government Regulation align with the flexibility of the legal institutions of Khiyar Ru'yah, Khiyar 'Aib, and Khiyar Syarat. The formal differences lie in the theological-moral foundation of khiyar versus the positivistic-secular nature of the UUPK, as well as the operational focus of khiyar on the independent status of contractual choice versus the UUPK's emphasis on strict liability following a loss. This study concludes that the architecture of modern digital e-commerce (features such as returns, refunds, and escrow accounts) actually facilitates the operational implementation of classical khiyar concepts, such that the harmonization of these two systems can strengthen the moral legitimacy and legal certainty of the digital commerce ecosystem in Indonesia.